Short Communication: In vitro evaluation of the abrasiveness of acidic dentifrices - Alves, K. M.; Pessan, Juliano Pelim [UNESP]; Buzalaf, M. A.; Delbem, Alberto Carlos Botazzo [UNESP] (My University, 2009)
AIM: This in vitro study evaluated the abrasiveness of acidic fluoride (F) dentifrices with different F concentrations on bovine enamel. METHODS: Enamel blocks (4.0 x 4.0 mm2, n=120) were selected according to their surface microhardness and divided into 12 groups. Slurries of dentifrices were used containing 0 (placebo), 275, 412, 550 and 1,100 ppm F (pH 4.5 or 7.0), as well as testing two commercial dentifrices (Crest, positive control, 1,100 ppm F and Colgate Baby, 500 ppm F). Enamel blocks were partially protected with an adhesive tape (control area) and then brushed by an automated toothbrushing machine (16,000 strokes). During this process, 0.4 ml of the slurries were injected every 2 mins on the enamel blocks. After toothbrushing, enamel wear was determined by profilometry. STATISTICS: Results were analyzed by ANOVA and Tukey's test (p<0.05). RESULTS: The mean values for pH in the suspensions during treatment were 6.93, 4.32, 7.56 and 8.19 for neutral experimental dentifrices, acidic experimental dentifrices, Crest and Colgate baby, respectively. The abrasiveness of the acidic dentifrices was similar (p<0.05) to the neutral ones, whereas commercial dentifrices yielded lower abrasion (p<0.05). CONCLUSION: It was concluded that a reduction of the pH of dentifrices does not increase their abrasiveness.
Keywords: acidulated fluorophosphate; anticaries agent; Crest Regular Dentifrice; fluoride sodium; placebo; silicon dioxide; toothpaste; animal; cattle; chemistry; comparative study; enamel; instrumentation; materials testing; pathology; pH; randomization; tooth brushing; tooth disease; Acidulated Phosphate Fluoride; Animals; Cariostatic Agents; Cattle; Chemistry, Pharmaceutical; Dental Enamel; Dentifrices; Hydrogen-Ion Concentration; Materials Testing; Placebos; Random Allocation; Silicon Dioxide; Sodium Fluoride; Tooth Abrasion; Toothbrushing; Toothpaste